Корекція ендотоксикозу і синдрому пероксидації у хворих на подагру в поєднанні з неалкогольним стеатогепатитом = Lipid peroxidation and endotoxemia syndrome сorrection in patients with gout combined with nonalcoholic steatohepatitis - Smiyan, S. I.; Danchak, S. V. (Journal of Education, Health and Sport, 2015)
Smiyan S. I., Danchak S. V. Корекція ендотоксикозу і синдрому пероксидації у хворих на подагру в поєднанні з неалкогольним стеатогепатитом = Lipid peroxidation and endotoxemia syndrome сorrection in patients with gout combined with nonalcoholic steatohepatitis. Journal of Education, Health and Sport. 2015;5(10):191-198. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32608 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A191-198 https://pbn.nauka.gov.pl/works/661416 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Корекція ендотоксикозу і синдрому пероксидації у хворих на подагру в поєднанні з неалкогольним стеатогепатитом Lipid peroxidation and endotoxemia syndrome сorrection in patients with gout combined with nonalcoholic steatohepatitis S. I. Smiyan, S. V. Danchak Department of Internal Medicine №2 (Head of Department. - MD, prof. Smiyan S.I.) Ternopil State Medical University named after I. Gorbachevsky, Communal establishment Ternopil Regional Council "Ternopil University Hospital", Ternopil, Ukraine. Aim. Patients with gout in 25% cases has signs of liver damage (clinical and instrumental data) and it’s proved that metabolic disorders plays main role in this process. Methods and results. A 120 patients with gout were examined, the diagnosis of nonalcoholic fatty liver disease confirmed by share wave elastography. Level of superoxide dismutase, catalase, ceruloplasmin, reduced glutathione and malonic dialdehyde where determined to assess the activity of antioxidant protection system and lipid peroxidation. Middle mass molecules indicated endogenous intoxication. Conclusion. Patients with gout in combination with nonalcoholic steatohepatitis is characterized by intensification of lipid peroxidation and decrease of antioxidant protection system, accompanied by of endotoxemia syndrome, which manifests with accumulation of lipid peroxidation products with high activity of free radical processes. Influenced by complex of treatment with fortified soy phospholipids and L-glutathione, significantly (p <0.001) reduced lipid peroxidation activity, appeared tendency to normalization of antioxidant protection and reduced the intensity of endotoxemia syndrome. Key words: gout, lipid peroxidation, endotoxemia, steatohepatitis.